ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PEMBEAJARAN IPAS DI SD NEGERI BULAN SELOPAMPANG KABUPATEN TEMANGGUNG - Sri Wahyu Utari; Puji Winarti; Nimas Puspitasari (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2024)
This research is motivated by the implementation of the independent curriculum in the science and science learning process. The focus of this research is the analysis of curriculum implementation in science and science learning. This research aims to describe in detail the implementation of the independent curriculum in the science and science learning subjects at the Bulan Selopampang Temanggung Elementary School. The type of research used is qualitative research. This research uses triangulation techniques, checking data through interviews, observation and documentation Based on the results of the analysis and discussion, looking at the three aspects of the implementation of the independent curriculum, namely project-based learning through strengthening the Pancasila student profile, focus on essential material, and flexibility for teachers and students, it can be concluded that the implementation of the independent curriculum in the science and science learning subjects At SD Negeri Bulan Selopampang Temanggung it is said that they are very deep in the science and science learning process. Keywords: Implementation of the Independent Curriculum, IPAS